A Multidisciplinary Approach to Open Access Village Telecenter Initiatives: the case of Akshaya - JOYOJEET PAL, SERGIU NEDEVSCHI, RABIN K. PATRA & ERIC A. BREWER (E-Learning, Volume 3, Number 3, 2006, 2006)
The Akshaya project in the rural Malappuram district of Kerala, India is home to the first and largest district-wide e-literacy project in India, and one of the largest known Internet Protocol-based networks. Through a network of 600 kiosks, the project has been designed to reach computer literacy into over 600,000 households, and bring 3.6 million residents of the district into regular affordable access to computer use. This study uses a regional analysis of Malappuram, and its parent state, to understand the context within which the project is situated and consider questions of generalizability from inferences drawn here. Second, the authors examine the technical network itself and read logs of how residents of the district are actually using the kiosks to discuss the case for content tailored to low-income users, and the larger case of state-underwritten shared-access computer centers.